Heidegger and Nietzsche - Babich, Babette E., 1956-; Denker, Alfred, 1960-; Zaborowski, Holger, 1974- (Elementa, 2012)
This volume contains new and original papers on Martin Heidegger's complex relation to Friedrich Nietzsche's philosophy. The authors not only critically discuss the many aspects of Heidegger's reading of Nietzsche, they also interpret Heidegger's thought from a Nietzschean perspective. Here is presented for the first time an overview of not only Heidegger's and Nietzsche's philosophy but also an overview of what is alive - and dead - in their thinking. Many authors through a reading of Heidegger and Nietzsche deal with current issues such as technology, ecology, and politics. This volume is of interest for everyone interested in Heidegger's and Nietzsche's thought. Contributors include: Babette Babich, Charles Bambach, Robert Bernasconi, Virgilio Cesarone, Stuart Elden, Michael Eldred, Markus Enders, Charles Feitosa, Véronique Fóti, Luanne T. Frank, Jeffery Kinlaw, Theodore Kisiel, William D. Melaney, Eric Sean Nelson, Abraham Olivier, Friederike Rese, Karlheinz Ruhstorfer, Harald Seubert, Robert Sinnerbrink, Robert Switzer, Jorge Uscatescu Barrón, Nancy A. Weston, Dale Wilkerson, Angel Xolocotzi, Jens Zimmermann